Review of Female Entrepreneurs Navigating the E-Commerce Landscape (International Journal of Food and Nutritional Sciences, 2022)
In the rapidly evolving world of e-commerce, female entrepreneurs are playing an increasingly significant role. This abstract explores the dynamics and challenges faced by women venturing into the e-commerce environment. Despite the opportunities presented by digital platforms, women encounter unique obstacles in establishing and scaling their online businesses. Cultural norms, access to funding, and gender biases often hinder their progress. Balancing professional pursuits with familial responsibilities adds another layer of complexity. female entrepreneurs are also leveraging their strengths to thrive in this competitive arena. Many are adept at building authentic connections with customers, leveraging social media, and fostering communities around their brands. Collaborative networks and mentorship programs tailored to women are emerging as valuable resources for navigating these challenges. By harnessing technology, resilience, and innovation, women entrepreneurs are reshaping the e-commerce landscape and challenging traditional business models. This abstract highlights the importance of recognizing and addressing the unique barriers faced by female entrepreneurs in e-commerce. By fostering an inclusive ecosystem that supports diversity and gender equality, we can unlock the full potential of women in driving economic growth and innovation in the digital marketplace.